A pediatric case of Stevens‐Johnson syndrome with acute liver failure, resulting in liver transplantation. Issue 9 (21st May 2021) - Totsuka, Michiru; Watanabe, Tomoya; Takamura, Naoko; Watanabe, Yuko; Kumamoto, Takafumi; Honda, Yasushi; Yoneda, Masato; Saito, Satoru; Yamanaka, Shoji; Aihara, Michiko
Abstract: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are fatal adverse skin reactions characterized by high fever, epidermal detachment, and mucositis. It is well known that SJS/TEN occasionally affects various organs, leading to permanent damage and death in some patients. Although acute liver dysfunction is a relatively common complication of SJS/TEN, severe acute liver dysfunction requiring liver transplantation is rare. We present the case of a 14‐year‐old girl with SJS complicated by severe and rapidly progressive liver dysfunction, specifically, acute liver failure (ALF) requiring liver transplantation. A lymphocyte transformation test showed positive results for acetaminophen and cefdinir. Furthermore, human leukocyte antigen (HLA) genotyping revealed the presence of the HLA‐A*02:06 genotype, which is reported to be strongly associated with acetaminophen‐related SJS/TEN with severe ocular complications. These results suggested that our patient may have presented with acetaminophen‐induced SJS complicated by ALF, but no ocular complications. This is the first report of a pediatric patient with SJS who required liver transplantation. In rare instances, severe liver dysfunction requiring liver transplantation should be considered as a possible complication of SJS/TEN.